콜로이드 자기조립법에 의해 제조된 다공질 구형 타이타니아 분말의 광촉매 특성 - 오인애; In-ae Oh; 신철환; Cheol Hwan Shin; 조영상; Young-sang Cho (대한금속·재료학회지, 54(8), 2016)
Macroporous titania crystallites were synthesized using an emulsion-assisted self-assembly method to prepare a photocatalyst for the decomposition of organic dyes such as methylene blue. The porous structure was prepared using polymeric particles as sacrificial templates, which were synthesized by large-scale dispersion polymerization. An in-depth study was performed to characterize the photocatalytic performance of the porous spherical titania particles by evaluating the rate constants of the decomposition reactions. Factors affecting the reaction rates were studied by controlling the size of macropores, the average diameter of the porous particles, the amount of photocatalysts and methylene blue in reaction mixture, and the power of the UV light sources. Enhanced photocatalytic performances were also observed for porous particles with hollow microstructure obtained using a rotating cylinder system, or bimodal porous particles. (Received February 2, 2016; Accepted March 31, 2016)